The accuracy of delivery of target pressures using self‐inflating bag manometers in a benchtop study. (June 2016) - Rafferty, Anthony R.; Johnson, Lucy; Maxfield, Dominic; Dawson, Jennifer A.; Davis, Peter G.; Thio, Marta
Abstract: Aim: We tested whether operators using manometers attached to self‐inflating bags could accurately deliver set targeted peak inspiratory pressures (PIPs) compared to the Neopuff ™ T‐piece resuscitator (TPR). Methods: Participants provided positive pressure ventilation to a leak‐free neonatal test lung at a rate of 60 inflations/min and a flow of 8 L/min. Participants used three manometers attached to self‐inflating bags and a Neopuff ™ TPR to target PIPs of 20, 30 and 40 cmH2 O on each device. Mean PIPs delivered with each manometer were compared to the 'gold standard' Neopuff ™ TPR. Results: In total, 13 991 inflations delivered by 20 participants were analysed. At all target PIPs, the mean PIP delivered using the Mercury Medical manometer attached to a Laerdal self‐inflating bag was significantly higher by 5 cmH2 O (p < 0.01) than the Neopuff ™ TPR. The PIP delivered using both the Ambu ™ and Parker Healthcare manometers attached to their respective devices was similar to that delivered by the Neopuff ™ TPR at all targeted PIPs. Conclusion: Accurately targeted PIPs can be achieved when a manometer specifically designed for use on a self‐inflating bag is used during manual ventilation. This may be useful in settings where access to a Neopuff ™ TPR or a gas flow source is limited.